A quality improvement intervention to enhance performance and perceived confidence of new internal medicine residents. Issue 4 (4th July 2018) - Otokiti, Ahmed; Sideeg, Abdelhaleem; Ward, Paulisa; Dongol, Merina; Osman, Mohamed; Rahaman, Oloruntobi; Abid, Syed
ABSTRACT: Background : Orientation for new medical residents is challenging due to the diversity of prior experiences and cultural backgrounds and is compounded by a lack of orientation curricula that adequately addresses the needs of the medical residents to allow them to perform their duties in an efficient manner from the start. The beginning of residency training is associated with reduced quality of healthcare widely referred to as the 'July effect'. Objective : To assess the impact of a peer-led orientation for new interns on (a) self-reported confidence level, (b) improvement in performance of first-year residents in appropriate clinical documentation and efficient discharge procedures and protocols. Design/methods : In June 2016, a hybrid of interactive teaching and simulation exercises was used to teach documentation of critical information, such as discharge medication reconciliation and discharge summary. A handout of an intern guide/manual was also provided. The previous year's data served as comparison/control data. Comparison data were obtained for both groups from hospital's utilisation review department. Results : Twenty-one of 23 expected new interns (91%) participated in the intervention. There was a significant decrease in non-compliance for clinical documentation in the intervention group compared to the control group. The self-reported confidence level in the intervention group increased 34%. Conclusions : Such peer-to-peer orientation has the potential to effectively improve appropriate documentation and discharge process by new residents and may help to reduce the 'July effect'.